Prediksi Jumlah Sampel Tes PCR Covid-19 Menggunakan Metode Single Moving Average - Nilam Fadhilah; Rachman Arief (Bulletin of Informatics and Data Science, 2022)
Covid-19 has spread all over the world. This virus was first discovered in the city of Wuhan, China. To avoid this virus, the community has implemented several strategies such as wearing masks, washing hands and conducting swab tests to determine whether the results are contaminated with the Covid-19 virus or not. In Indonesia, swab tests have been provided, such as the Antigen swab test and the PCR swab test. However, WHO recommends a PCR swab test because the results are more accurate. Until now, Indonesia has not been able to meet the minimum number of PCR test samples according to the WHO (World Health Organization) version, which is 1 per 1,000 people every week. Therefore, the purpose of this researcher is to create a system to predict the rise and fall of the number of daily PCR test samples at laboratories in West Java in the future. This research was conducted in West Java because the capacity of the number of PCR test samples was not optimal, only relying on manuals with limited human resources. Therefore, the authors are able to predict the number of PCR test samples in the future using the Single Moving Average method. This method takes a group of observations and looks for the average value of the daily development of the number of PCR test samples in West Java, as a forecast in the future. The number of Covid-19 PCR test samples from the MSE (Mean Square Error) calculation is 689,873. With the SMA method, it makes it easier for admins to see predictions for the number of PCR samples for the future.